Translation as communication across languages and cultures - House, Juliane (Routledge, Taylor & Francis Group, 2016)
In this interdisciplinary book, Juliane House breaks new ground by situating translation within Applied Linguistics. Featuring an account of translation from a linguistic-cognitive perspective, House covers problematic issues such as the existence of universals of translation, cases of untranslatability and ways and means of assessing the quality of a translation.